2013
DOI: 10.1186/1471-2458-13-738
|View full text |Cite
|
Sign up to set email alerts
|

“Moving forward: a cross sectional baseline study of staff and student attitudes towards a totally smoke free university campus”

Abstract: BackgroundBaseline data were collected to inform the adoption, implementation and institutionalisation phases of a completely smoke free campus policy at a large Western Australian university with a diverse student and staff community.MethodsAn online survey was randomly emailed to staff and students to measure the attitudes towards and the acceptability and enforcement of the policy prior to implementation. In total, 969 respondents completed the survey.ResultsGeneral attitudes towards smoking were negative. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 30 publications
4
51
0
1
Order By: Relevance
“…A study in Australia at Curtin University found similar results for student awareness of an institutional smokefree policy, with only 56% of students aware that the university had a tobacco policy (Burns et al, 2013). This is comparable to the current study, where 57.2% were aware of the smoke-free policy in Phase 2.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A study in Australia at Curtin University found similar results for student awareness of an institutional smokefree policy, with only 56% of students aware that the university had a tobacco policy (Burns et al, 2013). This is comparable to the current study, where 57.2% were aware of the smoke-free policy in Phase 2.…”
Section: Discussionsupporting
confidence: 77%
“…A study in Saudi Arabia (Almutairi, 2014) showed strong support among nonsmokers for a total ban at a university (97.4% of students, 75.3% of academics, and 87.4% of staff), while support among smokers was significantly lower (75.1% of students, 63.2% of academics and 26.1% of staff). In another study, the support for a total smoking ban at Curtin University in Australia was lower than the above study, with 70.4% of staff and 74.7% of students agreeing that a completely smoke-free campus has a positive effect on quality of life (Burns et al, 2013). …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This method has been used successfully in other studies in this university. 23 The online survey yielded 1930 responses, and a further 628 students were randomly recruited by trained research assistants on campus market day. All data was collected in 2013 during July andAugust.…”
Section: Methodsmentioning
confidence: 99%
“…The current study used methods consistent with those previously conducted at this university [23] [25]. Participants were drawn from a random cross-sectional sample of 6000,undergraduate, internally enrolled students, aged 18 -24 years, studying at the main metropolitan campus of a large Australian university.…”
Section: Study Design and Proceduresmentioning
confidence: 99%